Digital Health in Saudi Arabia: A Descriptive Study of User Perspectives, Adoption Rates, Benefits, and Challenges of Digital Health Applications - Alia Almoajel; Nawaf Alnuwaysir; Adel Ghazzai Alotaibi; Hanan Alzaidi; Haifa Alturki; Reem Alsaeed; Waleed Alsubhan; Mohammed Almadhi; Mohammed Muhawwis; Shabana Tharkar (The Journal of Medicine, Law & Public Health)
Background: Digital health applications have emerged as transformative tools within healthcare systems globally. This study investigates the perceptions, adoption, perceived benefits and challenges, and factors involved in the selection of digital health apps among the residents of Riyadh city, Saudi Arabia.